2014
DOI: 10.1016/j.ymgme.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis type II: Identification of 30 novel mutations among Latin American patients

Abstract: In this study, 103 unrelated South-American patients with mucopolysaccharidosis type II (MPS II) were investigated aiming at the identification of iduronate-2-sulfatase (IDS) disease causing mutations and the possibility of some insights on the genotype-phenotype correlation The strategy used for genotyping involved the identification of the previously reported inversion/disruption of the IDS gene by PCR and screening for other mutations by PCR/SSCP. The exons with altered mobility on SSCP were sequenced, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 47 publications
11
42
2
Order By: Relevance
“…Specifically, the above mutations have also been found in the Asian population such as in Chinese and Japanese patients [4, 25, 26] presenting with the severe phenotype. The published nonsense mutations, p.Q75*, p.W109*, and p.R172*, were found in our patients with severe phenotypes and were in agreement with previous literature reports among Caucasian and Asian patients with Hunter syndrome in terms of their effects on phenotype [19, 20, 2729]. Mutations introducing premature translation termination codons trigger nonsense-mediated decay, which prevents the synthesis of an abnormal protein, and have commonly been classified as severe mutations [4].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the above mutations have also been found in the Asian population such as in Chinese and Japanese patients [4, 25, 26] presenting with the severe phenotype. The published nonsense mutations, p.Q75*, p.W109*, and p.R172*, were found in our patients with severe phenotypes and were in agreement with previous literature reports among Caucasian and Asian patients with Hunter syndrome in terms of their effects on phenotype [19, 20, 2729]. Mutations introducing premature translation termination codons trigger nonsense-mediated decay, which prevents the synthesis of an abnormal protein, and have commonly been classified as severe mutations [4].…”
Section: Discussionsupporting
confidence: 93%
“…Some involved exon 3 of IDS; the premRNA region of this exon is particularly vulnerable to defects in splicing regulation. In the present work, functional analysis based on reporter minigenes was performed for two exon 3 nucleotide changes, c.257C N T [29][30][31] and c.241C N T [32], which confirmed these to be involved in exon 3 splicing dysregulation. Further, mutant minigene analysis and overexpression assays revealed that the SRSF2 (formerly SC35) and hnRNP E1 proteins might be involved in the use and repression of the constitutive 3′ splice site of exon 3 respectively.…”
Section: Introductionsupporting
confidence: 71%
“…Table 1 shows the genetic defects carried by the patients. Patient 1 was hemizygous for a nucleotide change in exon 3, c.241C NT (p.Q81X) already erroneously reported as p.Q80R by Brusius-Facchin et al [32]. A detailed analysis of the codon in the HGMD database (Professional 2014.3 Release) showed the mutation reported by these authors was, in fact, Q81X.…”
Section: Antisense Oligonucleotide Treatment and Analysismentioning
confidence: 93%
“…The patient described here is one of the youngest MPS II patients to have received HSCT so far; there is one patient reported to have been transplanted at 1.5 month [26]. Our described patient had the prediction of a severe phenotype proven both by the family history and the genotype [17], [18], [19].…”
Section: Discussionmentioning
confidence: 71%
“…Undetectable iduronate-2-sulphatase (I2S) activity and the familial p.Arg88His mutation on exon 3 (p.R88H) were detected in fibroblasts of the amniotic fluid. This is a missense mutation already reported and associated with the severe phenotype of MPS II [17], [18], [19].…”
Section: Case Reportmentioning
confidence: 79%